2013
DOI: 10.1186/1532-429x-15-61
|View full text |Cite
|
Sign up to set email alerts
|

Real-time cardiovascular magnetic resonance subxiphoid pericardial access and pericardiocentesis using off-the-shelf devices in swine

Abstract: BackgroundNeedle access or drainage of pericardial effusion, especially when small, entails risk of bystander tissue injury or operator uncertainty about proposed trajectories. Cardiovascular magnetic resonance (CMR) might allow enhanced imaging guidance.Methods and resultsWe used real-time CMR to guide subxiphoid pericardial access in naïve swine using commercial 18G titanium puncture needles, which were exchanged for pericardial catheters. To test the value of CMR needle pericardiocentesis, we also created i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 17 publications
(18 reference statements)
0
13
0
1
Order By: Relevance
“…39,40 A comparison between these needles demonstrates favorable results for active tracking. Active needles needed shorter access time (88 versus 244 s; P=0.022) and required significantly fewer needle passes (4.5 versus 9.1; P=0.028).…”
Section: Pericardial Needlesmentioning
confidence: 97%
See 1 more Smart Citation
“…39,40 A comparison between these needles demonstrates favorable results for active tracking. Active needles needed shorter access time (88 versus 244 s; P=0.022) and required significantly fewer needle passes (4.5 versus 9.1; P=0.028).…”
Section: Pericardial Needlesmentioning
confidence: 97%
“…In addition, a recent animal study demonstrated the feasibility of performing pericardiocentesis inside the scanner room using commercially available needles. 39 In total, 12 successful procedures (no complications) were performed using a realtime imaging approach and passive tracking of the needle. This development increases the practicability of complex ablative therapy in the scanner and significantly expands the emergency solving capacity of iCMR.…”
Section: Tamponadementioning
confidence: 99%
“…Passive visualization uses the intrinsic material properties. For example, metallic devices (e.g., biopsy needles, guidewires, stents, occluders) create a signal void on real-time MR images because they distort the local magnetic field, leading to local signal dephasing 56 . Signal voids can be emphasized using long TE gradient echo sequences.…”
Section: Imaging Protocolsmentioning
confidence: 99%
“…In patients with pulmonary hypertension, a lack of right ventricular functional augmentation and pulmonary vascular resistance reduction neous transthoracic left ventricular access for delivery of large devices, 45 direct transthoracic ventricular septal defect closure, 46 atrial septal puncture and balloon septostomy, 47 aortic coarctation stenting, 48 and MRIguided pericardiocentesis. 49 The great advantage of MRI over radiographic fl uoroscopy is the ability to view the interaction of devices with the surrounding tissue in real time. For example, while deploying stents or stent grafts or cardiac implants, the operator can watch for and address iatrogenic rupture, dissection, or pericardial tamponade.…”
Section: From Diagnostic To Interventional Mri Catheterizationmentioning
confidence: 99%